A survey on employee satisfaction level in the implementation of quality management initiatives - Wee, Shu Hui; Mahat, Mohd Amran; Ibrahim, Ilmiah (2011)
Choosing the right approach for quality management initiatives is critical and represents a continuous challenge for management success these days. Adopting inappropriate strategy may pose disastrous implications to the success of an organization. For example, failure to incorporate long-term view of success may lead to disagreement and conflict between raters and rates in performance evaluation. Employees, in particular, are regarded as the key attributes in most successful quality management initiatives of an organization. It is believed that achieving a sustainable quality management initiatives require organizational-wide participation as well as strong commitment from employees. Despite its importance, employee's satisfaction has often been neglected in the pursuance of quality management objectives (Hoque, 2003). This study aimed (i) to identify the level of employee satisfaction in the midst of quality management focus in an education institution, and (ii) to assess the level of employees' involvement with the quality management initiatives introduced by the top management. We used a survey to collect data. Survey questionnaires were personally administered on 207 respondents from academic and non academic staff in one of the public universities in Malaysia. The findings revealed that the mean score on employee satisfaction for female respondents is higher than the male. The result also suggests that respondents with more than 10 Years of Services are more satisfied and believed to have made greater contribution towards quality management initiatives. It is also remarkably noted that, 100% of respondents with more than 10 years of services had also involved with the quality management initiatives. The survey evidence provided by respondents in this study could assist decision makers in designing, executing and aligning, more practical, relevant as well as high impact strategies towards achieving sustainable quality management initiatives objectives. Comparatively lower satisfaction scores among new and male employees in the institution, as indicated by respondents in this study, suggests that new measures may need to be introduced by the management to improve the situation.